2014
DOI: 10.1128/jb.01851-14
|View full text |Cite
|
Sign up to set email alerts
|

CysK2 from Mycobacterium tuberculosis Is an O -Phospho- l -Serine-Dependent S -Sulfocysteine Synthase

Abstract: bMycobacterium tuberculosis is dependent on cysteine biosynthesis, and reduced sulfur compounds such as mycothiol synthesized from cysteine serve in first-line defense mechanisms against oxidative stress imposed by macrophages. Two biosynthetic routes to L-cysteine, each with its own specific cysteine synthase (CysK1 and CysM), have been described in M. tuberculosis, but the function of a third putative sulfhydrylase in this pathogen, CysK2, has remained elusive. We present biochemical and biophysical evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…This outcome is consistent with our observation that exposure to low levels of H 2 S triggers an antioxidant response evident by upregulation of genes involved in cysteine metabolism (Fig. 5a, b) and antioxidant genes such as sodA and ahpC 49,50 ( Supplementary Fig. 10A), which permit rapid emergence from hypoxia.…”
Section: Role Of H 2 S Duringsupporting
confidence: 92%
“…This outcome is consistent with our observation that exposure to low levels of H 2 S triggers an antioxidant response evident by upregulation of genes involved in cysteine metabolism (Fig. 5a, b) and antioxidant genes such as sodA and ahpC 49,50 ( Supplementary Fig. 10A), which permit rapid emergence from hypoxia.…”
Section: Role Of H 2 S Duringsupporting
confidence: 92%
“…In addition, examples of OPSS enzymes not involved in l -Dap biosynthesis are known: CysM 45,57 and CysK2 58 from M. tuberculosis and CysO 28 from Aeropyrum pernix K1. OPS is the preferred substrate of both CysM and CysO, but unlike SbnA, they are also capable of reacting with OAS to generate the PLP-α-aminoacrylate intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…45 CysK2 behaves more like SbnA, with specificity for OPS alone. 58 The CysM and CysO crystal structures have comparable active sites to SbnA except that SbnA is missing a loop that lies directly above the PLP cofactor. This loop contains a conserved arginine that is important for OPS specificity over OAS in CysM.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution of these isozymes for redundancy in the pathway step may have arisen because of the need of the microbe to survive under varying habitats (sulfide or thiosulfate rich) or for stress adaptation in some pathogens. For instance CysM appears to be the key enzyme for catalyzing the production of l-cysteine during dormant M. tuberculosis and maintaining intracellular redox homeostasis inside host macrophages (Steiner et al 2014). Similarly, it is reported that S. typhimurium lacking cysK and cysM is less virulent and exhibits reduced antibiotic resistance (Turnbull et al 2008(Turnbull et al , 2010.…”
Section: Introductionmentioning
confidence: 97%
“…CysK, the next enzyme of the pathway, uses pyridoxal 5′-phosphate (PLP) as a cofactor to convert OAS and sulfide into cysteine and acetate. There are other OASS present as well, designated CysM and CysK2, which are 43% and 26% identical to CysK, respectively, but catalyzes the formation of preferred O-phosphol-serine (OPS) with either CysO-SH sulfur donor in case of CysM or sulfide/sulphate donor in case CysK2 to produce cysteine via CysO-cysteine or S-sulfocysteine intermediates, respectively (Kredich 1996;Steiner et al 2014;Schnell et al 2015;Fig. 1).…”
Section: Introductionmentioning
confidence: 99%